2013
DOI: 10.1586/14779072.2013.839942
|View full text |Cite
|
Sign up to set email alerts
|

Investigational drugs targeting cardiac fibrosis

Abstract: Fibrosis is an accumulation of proteins including collagen in the extracellular space, which has previously been considered as irreversible damage in various cardiovascular diseases including heart failure and hypertension. The pathophysiology of fibrosis is currently better understood and can be evaluated by non-invasive methods. Here, the authors present briefly the impact and molecular mechanisms of fibrosis in the myocardium and the promising therapeutic candidates including anti-hypertensive therapies, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 127 publications
0
37
0
Order By: Relevance
“…Cardiac fibrosis is considered irreversible damage in various cardiovascular diseases, among them overt heart failure (HF) (Roubille et al, 2014). However, the diagnosis and potential treatments of cardiac fibrosis are limited.…”
Section: Gal-3 In Fibrotic Diseasesmentioning
confidence: 99%
“…Cardiac fibrosis is considered irreversible damage in various cardiovascular diseases, among them overt heart failure (HF) (Roubille et al, 2014). However, the diagnosis and potential treatments of cardiac fibrosis are limited.…”
Section: Gal-3 In Fibrotic Diseasesmentioning
confidence: 99%
“…Myocardial fibrosis is considered irreversible in a wide range of cardiovascular diseases, including overt HF [41]. Recent studies have shown that galectin-3 is involved in the proliferation and differentiation of myofibroblasts that further stimulate collagen synthesis.…”
Section: Myocardial Fibrosismentioning
confidence: 99%
“…Other targets, such as tissue fibrosis, may be left untreated [8] . Whether the presence of OSAS could impact the post-MI remodeling is unclear.…”
Section: Cardiac Remodelingmentioning
confidence: 99%